"Sharing is Caring": Online Self-disclosure, Offline Social Support, and Social Network Site Usage in the UAE. (September 2015) - Mohamed Ahmed, Azza Abdel-Azim
The Arab information about themselves through social networking sites and offline social support affect the pattern of online self-disclosure. The impact of the social network site (SNS), size of a user's pool of friends, the intensity of SNS usage, and attitudes toward online self-disclosure are examined through applied qualitative and quantitative research methodologies. A total of 313 Arab residents of the United Arab Emirates living in Dubai and Abu Dhabi formed the sample of a survey. Constructed in-depth interviews were conducted with 69 Arab residents in the UAE. The findings indicated a positive significant correlation between online self-disclosures and the diversity of SNS audience, while intensity of SNS usage did not correlate to online self-disclosure. The more respondents had emotional and informational offline support, the more they were likely to be "honest" in their online self-disclosure. Females are higher in social companionship, emotional, and informational forms of offline social support than males, while the latter are more likely to disclose personal information online than females. Males practice "parental authority" with females to protect them from possible dangers of online self-disclosure. In-depth interviews showed that SNS users carefully govern the amount of information they post on SNSs and to whom they make it available.